Synergistic effects of zinc borate and halloysite nanotubes (HNTS) on char morphology and gases emission of epoxy based intumescent fire retardant systems - Gillani, Q.F. (Asian Research Publishing Network, 2016)
In this study, Zinc Borate (ZB) and Halloysite nanotubes (HNTs) are simultaneously integrated in the in expandable graphite (EG) based intumescent fire retardant coatings. The synergistic effect between the ZB and HNTs on fire performance, char morphology, and thermal degradation of IFRC were investigated. The IFRC of ZB/HNTs (5.5:1.5) showed noticeable improvement in char quality. Similar ratio of incorporated additives showed significant reductions in the phenolic gasses emission of IFRC. FESEM results showed that a solid and dense char layer was formed in ZBH (5), which hindered the transfer of heat to substrate and hold combustible gases in the condensed phase reaction. It is concluded that the combination of ZB and HNTs is proved to be a supportive synergism in development of environment friendly intumescence coating systems. Â©2006-2016 Asian Research Publishing Network (ARPN).